PENGARUH DUKUNGAN MANAJEMEN PUNCAK, MANAJEMEN PROYEK DAN KETERLIBATAN PENGGUNA TERHADAP TINGKAT KESUKSESAN IMPLEMENTASI ENTERPRISE RESOURCE PLANNING PADA PERUSAHAAN DI JABODETABEK - Aristo, Julian (Economic Faculty, Attahiriyah Islamic University, 2017)
Enterprise Resource Planning (ERP) systems have become vital strategic tools in today’s competitive business environment. Implementation of ERP systems is a highly complex process which is influenced not only by technical, but also by other factors. The purpose of this research to find out factors influencing the success of ERP implementations in companies in Jabodetabek. In this research three factors of success implementation ERP were selected on the bases of previous research that includes top management support, project management and user involvement. The results indicate that top management support and project management are key factors affecting the success of ERP implementations, while user involvement does not affect the success of ERP implementations. Top management support, project management and user involvement affect the success rate of 72.7% of ERP implementations. While the rest equal to 27.3% influenced by other variables not included in this research model. Keywords: Enterprise Resource Planning, Top management support, project management, user involvement